Phase contrast and cardiac cine MRI for non-invasive assessment of hepatic haemodynamic and cardiac systolic function in a rodent model of chronic liver disease. (25th February 2016) - Chouhan, Manil; Bainbridge, Alan; Davies, Nathan; Walker-Samuel, Simon; Lythgoe, Mark; Mookerjee, Rajeshwar; Taylor, Stuart
Abstract: Background: Profound vascular changes occur in cirrhosis, but they are poorly understood because of the invasive methods required for measurement. In this study, we used non-invasive imaging to investigate hepatic haemodynamic and cardiac systolic variables in a rodent model of cirrhosis. Methods: A cross-sectional in-vivo study with 9.4T MRI was undertaken in sham and bile-duct ligated (BDL) rats after 4 weeks. Phase-contrast MRI was used to measure total liver blood flow, portal venous flow, and hepatic arterial flow (seven sham rats, nine BDL rats) and cardiac cine MRI to measure cardiac output, stroke volume, left ventricular ejection fraction (LVEF), and cardiac index (13 sham rats, 12 BDL rats). Unpaired t tests were used for comparisons. Ethics committee approval was obtained. Findings: Mean total liver blood flow and portal venous flow were higher in sham than in BDL rats (214·3 mL/min per 100 g [SD 44·1] vs 152·3 [56·0] p=0·0308, and 181·4 [31·9] vs 68·5 [30·5] p<0·0001, respectively) but hepatic arterial flow was higher in BDL than in sham rats (83·8 [57·4] vs 33·0 [29·9], p=0·0526). No significant difference in heart rate was demonstrated but mean stroke volume, cardiac output, LVEF, and cardiac index were higher in BDL than in sham rats (0·59 mL [0·12] vs 0·46 [0·07], p=0·0030; 197·6 mL/min [41·8] vs 151·4 [23·5], p=0·0022; 76·6% [9·5] vs 68·0 [9·3], p=0·0311; and 469·0 mL/min per kg [92·4] vs 313·0 [50·3], p<0·0001; respectively). No significant difference in total liver blood flow relative to cardiac output was demonstrated but hepatic arterial flow relative to cardiac output was higher in BDL than in sham rats (13·9% [7·1] vs 3·4 [2·4], p=0·0027). Interpretation: We found reduced total liver blood flow in BDL rats despite rises in hepatic arterial flow. BDL rats have features of cirrhotic cardiomyopathy and fail, despite increased liver to body-mass ratio, to increase hepatic perfusion demands from the systemic circulation. Our findings support further investigation of MRI biomarkers and monitoring for therapies to optimise systemic and hepatic haemodynamics in cirrhosis. Funding: Wellcome Trust (grant WT092186).